PERAN KELOMPOK TANI ORA ET LABORA DALAM PENINGKATAN PRODUKTIVITAS USAHATANI PADI SAWAH DI KELURAHAN TARATARA SATU - Syntia ., Pandey; Melsje Yellie Memah; Jean Fanny Junita Timban (Sam Ratulangi University, 2019)
This study aims to determine how the role of Ora et Labora Farmers Group in increasing the productivity of wetland rice farming in Taratara Satu Village, Tomohon Barat District, Tomohon City. The Ora et Labora Farmer Group was choose purposevly and all the board members and members of the Farmer Group as respondents. This study used primary data and secondary data. Primary data was carried out by direct interviews with 10 farmers who were members and board members of the Ora et Labora Farmer Group. Secondary data was obtained from the Taratara Satu Village Office in Tomohon Barat Subdistrict, local bookstores, the internet through google scholar to get electronic books, journal articles and theses that related to the research topic on the role of Farmer Groups in increasing productivity of lowland rice farming. The data analysis method used in this study is descriptive analysis and then interpreted to draw conclusions. The results showed that there was an increase in farm productivity compared to before joining the Ora et Labora farmer group. Ora et Labora farmer group has played a role in increasing the productivity of rice farming in farmer groups in Taratara Satu Village, Tomohon Barat Subdistrict, Tomohon City, therefore was classified to the good category.-*eprm*